(untitled) (Academia Science Repository, 2023)
Throughout history, people have used readily available energy sources such as wind, water, and muscle power for their daily needs. Solar energy is an inexhaustible source of renewable energy for mankind. In addition, it is clean energy and does not pollute the environment. Among the efficient use of solar energy, the use of solar photovoltaic is the fastest growing and most dynamic research field in recent years, and it is one of the most watched projects. In this article, we will talk about the basic working principle of solar cell technology and the direction and prospects of future development. Solar energy is a type of light energy that needs to be converted into electrical energy using an energy converter. This energy converter that converts solar energy (or other light energy) into electrical energy is called a solar cell.